The effects of aqueous extract of Labisia Pumila (Blume) Fern.-Vill. Var. Alata on wound contraction, hydroxyproline content and histological assessments in superficial partial thickness of second-degree burn model - Ibrahim, Nurul ‘Izzah; Mohamed, Isa Naina; Mohamed, Norazlina; Mohd Ramli, Elvy Suhana; Shuid, Ahmad Nazrun (Frontiers in Pharmacology, 2022)
Background: Burns are considered a critical care problem in emergency medicine, resulting in physical, psychological, and chronic disabilities. Silver sulfadiazine is the gold standard in topical burn treatment but was associated with toxicity to keratinocytes and fibroblasts, which may delay wound healing. In discovering potential alternative treatments for burn wound healing, this study was performed to determine the effect of Labisia Pumila (Blume) Fern.-Vill. Var. Alata (LPVa) extract on thermal-burn wounds in rats. Methods: A total of 50 Sprague-Dawley male rats were categorized into five groups. There were three control groups; normal control (left untreated), negative control (given ointment base) and positive control (given silver sulfadiazine). Meanwhile, the two intervention groups were given with 2% LPVa leaf and root extracts, respectively. Burn wounds were inflicted on the loin region of the rat by applying a heated steel rod at 80oC for 10 seconds. On days 3, 7, 14 and 21, wounds were measured macroscopically using a digital calliper and one animals of each group were sacrificed, and the wounded skin were excised for histomorphological assessments. The wounds were excised for hydroxyproline content on Day 14 of treatment. Result: For wound contraction percentage, both the leaf and root extracts of LPVa showed a significant reduction in burn wound size on Day 7 onwards, when compared to other groups. For hydroxyproline content, only the leaf extract of LPVa produced significantly higher content compared to both negative and normal control groups. In terms of histological examination, the leaf extract group demonstrated a superior healing effect than the root extract group. Conclusion: Both leaf and root extracts of LPVa could promote wound healing in the thermal-burn wound rat model, with leaf extract being superior to root extract.